Developing an international network for clinical research: the Community-Acquired Pneumonia Organization experience. (January 2011) - Peyrani, Paula; Wiemken, Timothy; Arnold, Forest; Ramirez, Julio
Clinical research can be defined as the generation of new knowledge in the medical field by performing studies that involve patients with a specific disease. The basic steps for the development of a clinical research network are: creation of a steering committee, development of a network core study, establishment of a network coordinating center, delineation of network research opportunities and definition of the publication policy. Models for international collaborations among clinical investigators will continue to emerge as a methodology for performing research on large numbers of subjects. A well-established network is a very effective mechanism in the generation of new knowledge in a particular medical field.